145k views
5 votes
Help pleasee
on the image
with the steps.​

Help pleasee on the image with the steps.​-example-1
User Jpaljasma
by
4.8k points

1 Answer

2 votes

Answer:

an = 22 -6(n -1)

Explanation:

The first term of the sequence is given as a1 = 22. The general term of an arithmetic sequence is ...

an = a1 +d(n -1) . . . . n-th term for first term a1 and common difference d

The third term will be ...

a3 = 10 = 22 +d(3 -1)

Then the common difference is ...

10 -22 = 2d

-12/2 = d = -6

__

Putting the known values into the formula for the general term, it becomes ...

an = 22 -6(n -1)

__

This can be simplified to ...

an = 28 -6n

User Pheon
by
4.6k points